Austenitic stainless steel sheet and method of manufacturing the same, and leaf spring
Patent Information
- Application Number
- KR1020247009476
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-06
- Filing Date
- 2022-10-20
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-10-20
Smart Images

Figure 112024031651501-PCT00001 
Figure 112024031651501-PCT00002 
Figure 112024031651501-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to an austenitic stainless steel sheet, a method for manufacturing the same, and a plate spring. Background Technology
[0002] Along with the miniaturization and increased performance of communication devices such as smartphones and precision devices such as computers, the structural and functional components used in these devices are becoming thinner and lighter. Consequently, materials used for these components are required to possess high strength even with a small thickness. In particular, in foldable smartphones (foldable phones), leaf springs are used in the backplates that support the folding function of the liquid crystal screen; therefore, components such as leaf springs exposed to repeated folding require fatigue characteristics capable of withstanding such repeated folding.
[0003] As a material used for components such as leaf springs, Patent Document 1 describes a stainless steel containing, in mass%, C: 0.10% or less, Si: greater than 1.0% to 4.0%, Mn: 2.0% or less, Ni: 4.0% to 10.0%, Cr: 12.0% to 18.0%, and N: 0.15% or less, and also C+N ≥ 0.10%, and also containing these elements such that the value of Md(N) according to the formula Md(N) = 580-520C-2Si-16Mn-16Cr-23Ni-300N-26Cu-10Mo is in the range of 20 to 70, with the remainder consisting of Fe and impurities inevitably incorporated during manufacturing, and exhibiting a metastable austenite phase in a solution treatment state, wherein the low temperature is from minus 20°C to 70°C and the reduction rate An austenitic stainless steel sheet is proposed that is manufactured by cold working at 30 to 70% to transform a portion of the austenite phase into work-induced martensite, and then performing an aging treatment at 300 to 650°C for 0.1 to 90 minutes.
[0004] Furthermore, as a material with excellent fatigue properties, Patent Document 2 comprises, in mass%, C: 0.15% or less, Si: 1.0~4.0%, Mn: 5.0% or less, Ni: 4.0~10.0%, Cr: 12.0~18.0%, Cu: 0~3.5% (including no addition), Mo: 1.0~5.0%, and N: 0.15% or less, satisfying C+N≥0.10% and Si+Mo≥3.5%, and additionally, the value of Md(N), defined as Md(N)=580-520×[%C]-2×[%Si]-16×[%Mn]-16×[%Cr]-23×[%Ni]-300×[%N]-26×[%Cu]-10×[%Mo], is in the range of 20~100, and the remainder is Fe A steel sheet composed of and unavoidable impurity elements, wherein precipitates are present in the steel sheet, the maximum size of the precipitates is 0.5 μm or less, and the tensile strength is 1800 N / mm 2 An austenitic stainless steel sheet of the above is proposed. Prior art literature
[0005] Japanese Patent Publication No. Hei 7-90372 Japanese Patent Publication No. Hei 10-140294 The problem to be solved
[0006] The austenitic stainless steel sheets described in Patent Documents 1 and 2 cannot be said to have sufficient strength when the thickness is small (especially when the thickness is 0.15 mm or less).
[0007] The present invention was made to solve the above-mentioned problems and aims to provide an austenitic stainless steel sheet having high strength and excellent fatigue properties even with a small thickness, and a method for manufacturing the same.
[0008] In addition, the present invention aims to provide a leaf spring that has high strength and a long lifespan even with a small thickness. means of solving the problem
[0009] As a result of conducting the aforementioned research, the inventors discovered that the above problem can be solved by controlling the composition and metal structure of an austenitic stainless steel sheet, and thus completed the present invention.
[0010] That is, the present invention comprises, on a mass basis, C: 0.04~0.11%, Si: 2.0~3.5%, Mn: 0.01~1.50%, Ni: 6.0~10.0%, Cr: 12.0~15.0%, Mo: 1.3~3.2%, Cu: 0.01~1.00%, N: 0.03~0.15%, O: 0.0001~0.0050%, and the remainder consists of Fe and impurities, and the following formula (1):
[0011] Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo ··· (1)
[0012] Md represented by (in the formula, the element symbol indicates the content (mass%) of each element) 30 It has a composition with a value of -30 to 0℃, and
[0013] It has a metal structure having a processed organic martensite phase content of 30.0 volume% or more, and also
[0014] It is an austenitic stainless steel sheet with a thickness of 0.15 mm or less.
[0015] In addition, the present invention comprises, on a mass basis, C: 0.04~0.11%, Si: 2.0~3.5%, Mn: 0.01~1.50%, Ni: 6.0~10.0%, Cr: 12.0~15.0%, Mo: 1.3~3.2%, Cu: 0.01~1.00%, N: 0.03~0.15%, O: 0.0001~0.0050%, and the remainder consists of Fe and impurities, and the following formula (1):
[0016] Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo ··· (1)
[0017] Md represented by (in the formula, the element symbol indicates the content (mass%) of each element) 30 For a hot-rolled annealed plate having a composition in which the value of is -30 to 0℃, an intermediate rolling annealing process in which the step of sequentially performing cold rolling and annealing is repeated two or more times, and
[0018] A temper rolling process for a cold-rolled annealed plate obtained from the above intermediate rolling annealing process, wherein temper rolling is performed at a rolling reduction rate of 60% or more to adjust the thickness to 0.15 mm or less, and
[0019] For the tempered rolled plate obtained from the above tempered rolling process, the following formula (2):
[0020] B=T(log t+20) ··· (2)
[0021] An aging treatment process in which the value of B, expressed by (where T is temperature (K) and t is time (h)), is 11,500 to 15,000.
[0022] This is a method for manufacturing an austenitic stainless steel sheet, including
[0023] In addition, the present invention is a plate spring comprising the austenitic stainless steel plate. Effects of the invention
[0024] According to the present invention, an austenitic stainless steel sheet having high strength and excellent fatigue properties even with a small thickness, and a method for manufacturing the same can be provided.
[0025] In addition, according to the present invention, a leaf spring with high strength and a long lifespan can be provided even with a small thickness. Specific details for implementing the invention
[0026] Hereinafter, embodiments of the present invention will be described in detail. The present invention is not limited to the following embodiments, and it should be understood that modifications, improvements, etc., appropriately applied to the following embodiments based on the ordinary knowledge of those skilled in the art, without departing from the spirit of the present invention, also fall within the scope of the present invention.
[0027] Additionally, in this specification, the "%" notation regarding components means "mass%" unless specifically stated otherwise.
[0028] The austenitic stainless steel sheet according to an embodiment of the present invention comprises C: 0.04~0.11%, Si: 2.0~3.5%, Mn: 1.50% or less, Ni: 6.0~10.0%, Cr: 12.0~15.0%, Mo: 1.3~3.2%, Cu: 1.00% or less, N: 0.03~0.15%, O: 0.0050% or less, and the remainder consists of Fe and impurities.
[0029] Herein, in this specification, "austenitic" means that the metallic structure at room temperature is mainly the austenite phase. Accordingly, "austenitic" also includes the inclusion of a small amount of phases other than the austenite phase (e.g., ferrite phase or martensite phase).
[0030] In addition, "impurities" refers to components that are incorporated due to raw materials such as ore and scrap, or various factors of the manufacturing process, when industrially manufacturing austenitic stainless steel sheets, and are permitted within a range that does not adversely affect the present invention. For example, unavoidable impurities that are difficult to remove, such as P or S, are also included in these impurities.
[0031] In addition, regarding the content of each element in this specification, "including xx% or less" means that it is xx% or less, but includes an amount exceeding 0% (in particular, exceeding the impurity level).
[0032] In addition, the austenitic stainless steel sheet according to an embodiment of the present invention comprises, if necessary, one or more selected from Co: 0.05~0.50%, Al: 0.15% or less, V: 0.0001~0.5000%, Ti: 0.01~0.50%, B: 0.0001~0.0150%, Nb: 0.001~0.100%, Mg: 0.0001~0.0030%, Ca: 0.0003~0.0100%, Sn: 0.001~0.500%, Pb: 0.0001~0.0100%, W: 0.0001~0.5000%, Zr: 0.0001~0.1000%, and REM: 0.0001~0.3000%. It can be included additionally. Accordingly, the austenitic stainless steel sheet according to an embodiment of the present invention comprises C: 0.04~0.11%, Si: 2.0~3.5%, Mn: 1.50% or less, Ni: 6.0~10.0%, Cr: 12.0~15.0%, Mo: 1.3~3.2%, Cu: 1.00% or less, N: 0.03~0.15%, O: 0.0050% or less, Co: 0.05~0.50%, Al: 0~0.15%, V: 0.0001~0.5000%, Ti: 0.01~0.50%, B: 0.0001~0.0150%, Nb: 0.001~0.100%, Mg: 0.0001~0.0030%, Ca: It can be expressed that the composition comprises one or more additionally selected from 0.0003~0.0100%, Sn: 0.001~0.500%, Pb: 0.0001~0.0100%, W: 0.0001~0.5000%, Zr: 0.0001~0.1000%, and REM: 0.0001~0.3000%, with the remainder being Fe and impurities.
[0033] Here, regarding the content of each element in this specification, "including 0~xx%" means xx% or less, and also includes 0% (in the case where it is not included).
[0034] Below, each component is explained in detail.
[0035] <C: 0.04~0.11%>
[0036] C is an interstitial element and contributes to high strength through work hardening and aging treatment. In addition, C is an element that stabilizes the austenite phase and is also effective in maintaining non-magnetism. However, if the C content is too high, it becomes hardened and becomes a factor that reduces cold workability. Therefore, the upper limit of the C content is set to 0.11%, preferably 0.10%, and more preferably 0.09%. Meanwhile, the lower limit of the C content is set to 0.04%, preferably 0.05%, and more preferably 0.06% from the perspective of refining costs.
[0037] <Si: 2.0~3.5%>
[0038] Si is an element used as a deoxidizer for stainless steel in the steelmaking process. In addition, Si also has the effect of improving hardenability during aging treatment. However, since Si has a large solid solution strengthening effect and also improves work hardenability by lowering stacking fault energy, if the Si content is too high, it becomes a factor that reduces cold workability. Therefore, the upper limit of the Si content is set to 3.5%, preferably 3.3%, and more preferably 3.0%. On the other hand, the lower limit of the Si content is set to 2.0%, preferably 2.1%, and more preferably 2.2% from the perspective of securing the above effects by Si.
[0039] <Mn: 1.50% 이하>
[0040] Mn is an element that forms oxide-based inclusions (MnO). In addition, Mn has a small solid solution strengthening effect, is an austenite-forming element, and has the effect of suppressing processing-induced martensite transformation. For this reason, the upper limit of the Mn content is set to 1.50%, preferably 1.40%, and more preferably 1.30%. Meanwhile, the lower limit of the Mn content is not particularly limited, but can be set to preferably 0.01%, more preferably 0.05%, and even more preferably 0.10%.
[0041] <Ni: 6.0~10.0%>
[0042] Ni is an element included to obtain the austenite phase at high temperatures and room temperatures. It is necessary to include Ni so that the material forms a metastable austenite phase at room temperature and induces a martensite phase upon cold rolling. If the Ni content is too low, a δ-ferrite phase is formed at high temperatures, and a martensite phase is formed during the cooling process to room temperature, making it impossible for the material to exist as a single austenite phase. Therefore, the lower limit of the Ni content is set to 6.0%, preferably 6.3%, and more preferably 6.5%. On the other hand, if the Ni content is too high, it becomes difficult to induce the martensite phase upon cold rolling. Therefore, the upper limit of the Ni content is set to 10.0%, preferably 9.5%, and more preferably 9.0%.
[0043] <Cr: 12.0~15.0%>
[0044] Cr is an element that improves the corrosion resistance of austenitic stainless steel sheets. In order to secure corrosion resistance suitable for structural parts or functional parts (especially leaf springs), the lower limit of the Cr content is set to 12.0%, preferably 12.5%, and more preferably 13.0%. On the other hand, if the Cr content is too high, cold workability is reduced. Therefore, the upper limit of the Cr content is set to 15.0%, preferably 14.8%, and more preferably 14.5%.
[0045] <Mo: 1.3~3.2%>
[0046] Mo is an effective element for improving the corrosion resistance of austenitic stainless steel sheets. In addition, Mo is also an effective element for suppressing the release of deformation generated during cold rolling. Recently, considering its use in structural or functional parts (especially leaf springs) where improved corrosion resistance or fatigue properties are required, the lower limit of the Mo content is set to 1.3%, preferably 1.5%, and more preferably 1.7%. On the other hand, since Mo is expensive, an excessive Mo content leads to an increase in manufacturing costs. Furthermore, δ-ferrite and α-ferrite phases are formed at high temperatures. Therefore, the upper limit of the Mo content is set to 3.2%, preferably 3.0%, and more preferably 2.8%.
[0047] <Cu: 1.00% 이하>
[0048] Cu is an element that has the effect of hardening stainless steel during aging treatment. However, if the Cu content is too high, hot workability is reduced, which causes cracking. Therefore, the upper limit of the Cu content is set to 1.00%, preferably 0.90%, and more preferably 0.80%. Meanwhile, the lower limit of the Cu content is not particularly limited, but can be set to preferably 0.01%, more preferably 0.02%, and even more preferably 0.03%.
[0049] <N: 0.03~0.15%>
[0050] N is an austenite-forming element. In addition, N is a very effective element for hardening the austenite and martensite phases. However, if the N content is too high, it causes blowholes during casting. For this reason, the upper limit of the N content is set to 0.15%, preferably 0.13%, and more preferably 0.12%. Meanwhile, the lower limit of the N content is set to 0.03%, preferably 0.05%, from the perspective of securing the above effect by N.
[0051] <O: 0.0050% 이하>
[0052] If the O content is too high, coarse inclusions with an average diameter exceeding 5 μm are likely to form. Therefore, the upper limit of the O content is preferably set to 0.0050%, more preferably to 0.0045%, and even more preferably to 0.0040%. On the other hand, the lower limit of the O content is not particularly limited, but if the O content is too low, Mn or Si, etc., become difficult to oxidize, and the proportion of Al2O3 in the inclusions increases. Therefore, the lower limit of the O content can be preferably set to 0.0001%, more preferably to 0.0010%, and even more preferably to 0.0020%.
[0053] <Co: 0.05~0.50%>
[0054] Co is an element contained in austenitic stainless steel sheets as needed. Co has the effect of improving resistance to gap corrosion. In order to exert this effect by Co, the lower limit of the Co content can be set preferably to 0.05%, more preferably to 0.08%, and even more preferably to 0.10%. On the other hand, if the Co content is too high, the austenitic stainless steel sheet becomes hardened and its ductility decreases. Therefore, the upper limit of the Co content can be set preferably to 0.50%, more preferably to 0.40%, and even more preferably to 0.30%.
[0055] <Al: 0.15% 이하>
[0056] Al is an element included in austenitic stainless steel sheets as needed. Al has a higher affinity for oxygen compared to Si and Mn. If the Al content is too high, coarse oxide-based inclusions that serve as initiation points for internal cracks during cold rolling are prone to forming. Therefore, the upper limit of the Al content can preferably be set to 0.15%, more preferably to 0.13%. Meanwhile, the lower limit of the Al content is not particularly limited, but since excessive low Al content leads to an increase in manufacturing costs, it can preferably be set to 0.01%, more preferably to 0.03%, and even more preferably to 0.05%.
[0057] <V: 0.0001~0.5000%>
[0058] V is an element contained in austenitic stainless steel sheets as needed. V is an element that has the effect of increasing age hardenability during aging treatment. In order to sufficiently obtain this effect, the lower limit of the V content can preferably be set to 0.0001%, more preferably to 0.0010%. On the other hand, if the V content is too high, it leads to an increase in manufacturing costs. Therefore, the upper limit of the V content can preferably be set to 0.5000%, more preferably to 0.4800%, and even more preferably to 0.4500%.
[0059] <Ti: 0.01~0.50%>
[0060] Ti is an element included in austenitic stainless steel sheets as needed. Ti is a carbonitride-forming element that fixes C and N and suppresses the decrease in corrosion resistance caused by sensitization. To achieve this effect, the lower limit of the Ti content can be set to preferably 0.01%, more preferably 0.03%, and even more preferably 0.05%. On the other hand, if the Ti content is too high, the solid solution capacity of C and N decreases, and it may precipitate as carbides with non-uniform sizes and localization, thereby inhibiting recrystallized grain growth. Furthermore, since Ti is expensive, it leads to an increase in manufacturing costs. Therefore, the upper limit of the Ti content can be set to preferably 0.50%, more preferably 0.40%, and even more preferably 0.30%.
[0061] <B: 0.0001~0.0150%>
[0062] B is an element contained in austenitic stainless steel sheets as needed. If the B content is too high, it becomes a factor that causes a decrease in workability due to the formation of borides. Therefore, the upper limit of the B content can preferably be set to 0.0150%, more preferably to 0.0100%. Meanwhile, the lower limit of the B content is not particularly limited, but can preferably be set to 0.0001%, more preferably to 0.0002%.
[0063] <Nb: 0.001~0.100%>
[0064] Nb is an element included in austenitic stainless steel sheets as needed. Nb is an element with a high affinity for C and N, and precipitates as carbides or nitrides during hot rolling, reducing dissolved C and dissolved N in the matrix phase, thereby improving workability. To achieve this effect, the lower limit of the Nb content can be set preferably to 0.001%, and more preferably to 0.005%. On the other hand, if the Nb content is too high, the austenitic stainless steel sheet becomes hardened, and ductility decreases. Therefore, the upper limit of the Nb content can be set preferably to 0.100%, and more preferably to 0.050%.
[0065] <Mg: 0.0001~0.0030%>
[0066] Mg is an element contained in austenitic stainless steel sheets as needed. Mg forms Mg oxide together with Al in the molten steel and acts as a deoxidizer. In order to exert this effect, the lower limit of the Mg content can be set preferably to 0.0001%, and more preferably to 0.0005%. On the other hand, if the Mg content is too high, the toughness of the austenitic stainless steel sheet decreases. Therefore, the upper limit of the Mg content can be set preferably to 0.0030%, and more preferably to 0.0020%.
[0067] <Ca: 0.0003~0.0100%>
[0068] Ca is an element contained in austenitic stainless steel sheets as needed. Ca has the effect of improving hot workability. In order to exert this effect of Ca, the lower limit of the Ca content can preferably be set to 0.0003%, more preferably to 0.0005%. On the other hand, if the Ca content is too high, the toughness of the austenitic stainless steel sheet decreases. Therefore, the upper limit of the Ca content can preferably be set to 0.0100%, more preferably to 0.0050%.
[0069] <Sn: 0.001~0.500%>
[0070] Sn is an element contained in austenitic stainless steel sheets as needed. Sn has the effect of improving workability by promoting the formation of deformation zones during rolling. In order to exert this effect of Sn, the lower limit of the Sn content can preferably be set to 0.001%, and more preferably to 0.003%. On the other hand, if the Sn content is too high, the effect of Sn becomes saturated and workability deteriorates. Therefore, the upper limit of the Sn content can preferably be set to 0.500%, and more preferably to 0.200%.
[0071] <Pb: 0.0001~0.0100%>
[0072] Pb is an element contained in austenitic stainless steel sheets as needed. Pb has the effect of improving machinability. In order to exert such effects due to Pb, the lower limit of the Pb content can preferably be set to 0.0001%, and more preferably to 0.0005%. On the other hand, if the Pb content is too high, it lowers the melting point of the grain boundaries and reduces the bonding strength of the grain boundaries, which may lead to a deterioration in hot workability, such as liquefaction cracking caused by grain boundary melting. Therefore, the upper limit of the Pb content can preferably be set to 0.0100%, and more preferably to 0.0080%.
[0073] <W: 0.0001~0.5000%>
[0074] W is an element contained in austenitic stainless steel sheets as needed. W has the effect of improving high-temperature strength without impairing ductility at room temperature. In order to exert such effects by W, the lower limit of the W content can preferably be set to 0.0001%, and more preferably to 0.0005%. On the other hand, if the W content is too high, coarse eutectic carbides are formed, causing a decrease in ductility. Therefore, the upper limit of the W content can preferably be set to 0.5000%, and more preferably to 0.4500%.
[0075] <Zr: 0.0001~0.1000%>
[0076] Zr is an element contained in austenitic stainless steel sheets as needed. Zr is an element with a high affinity for C and N, and precipitates as carbides or nitrides during hot rolling, reducing dissolved C and dissolved N in the matrix phase, thereby improving workability. To achieve this effect, the lower limit of the Zr content can be set preferably to 0.0001%, and more preferably to 0.0005%. On the other hand, if the Zr content is too high, the austenitic stainless steel sheet becomes hardened, and ductility decreases. Therefore, the upper limit of the Zr content can be set preferably to 0.1000%, and more preferably to 0.0500%.
[0077] <REM: 0.0001~0.3000%>
[0078] REM is an element contained in austenitic stainless steel sheets as needed. REM (elements with atomic numbers 21, 39, 57 to 71, such as La, Ce, and Nd) has the effect of improving high-temperature oxidation resistance. In order to exert such effects from REM, the lower limit of the REM content can preferably be set to 0.0001%, and more preferably to 0.0010%. On the other hand, if the REM content is too high, the effect from REM becomes saturated, and surface defects occur during hot rolling, which reduces manufacturability. Therefore, the upper limit of the REM content can preferably be set to 0.3000%, more preferably to 0.1000%, and even more preferably to 0.0500%. REM may be a single element or a combination of multiple different elements.
[0079] <Md 30 -30~0℃>
[0080] Md 30 Silver represents the temperature (°C) at which 50% of the microstructure transforms into martensite when a strain of 0.30 is applied to the austenite (γ) single phase. Therefore, Md30 The higher this value (higher temperature), the more unstable the austenite is.
[0081] Md 30 It is represented by the following equation (1).
[0082] Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo ··· (1)
[0083] In the formula, the element symbol indicates the content (mass%) of each element.
[0084] Md 30 If this is too low, the stability of the austenite phase increases, making it difficult to transform the austenite phase into the work-induced martensite phase by cold rolling, and thus sufficient high strength cannot be achieved. Therefore, Md 30 The lower limit of is set to -30℃. Meanwhile, Md 30 If this is too high, the austenite phase becomes unstable, and as the amount of work-induced martensite phase transformed by cold rolling increases, it becomes difficult to control the dislocation density of each phase described below to the desired range, so the desired ductility or fatigue properties cannot be obtained. Therefore, Md 30 The upper limit of is set to 0℃.
[0085] An austenitic stainless steel sheet according to an embodiment of the present invention has a metal structure in which the content of the processing-induced martensite phase is 30.0 volume% or more. By controlling the content of the processing-induced martensite phase within this range, the strength and fatigue properties of the austenitic stainless steel sheet can be improved. Furthermore, from the perspective of stably obtaining this effect, the content of the processing-induced martensite phase is preferably 30.5 volume% or more, and more preferably 31.0 volume% or more. In addition, the upper limit of the content of the processing-induced martensite phase is not particularly limited, but is preferably 70.0 volume%, and more preferably 65.0 volume%.
[0086] Here, the content of the processed organic martensite phase can be measured using methods known in the relevant technical field. For example, the content of the processed organic martensite phase can be measured using a ferritescope or the like.
[0087] In the austenitic stainless steel sheet according to an embodiment of the present invention, it is preferable that the average crystal grain size is 15.0 μm or less. By controlling the average crystal grain size within this range, it becomes easier to improve the strength and fatigue properties of the austenitic stainless steel sheet. From the perspective of stably obtaining this effect, the average crystal grain size is more preferably 12.0 μm or less, and even more preferably 10.0 μm or less. In addition, the lower limit of the average crystal grain size is not particularly limited, but is preferably 1.0 μm, and more preferably 3.0 μm.
[0088] Here, the average crystal grain size can be measured in accordance with JIS G0551:2020.
[0089] An austenitic stainless steel sheet according to an embodiment of the present invention has a dislocation density of 0.40 × 10⁻⁶ of the residual austenite phase. 16 m -2 It is desirable that it be above this range. By controlling the dislocation density of the retained austenite phase within this range, the strength and fatigue strength of the austenitic stainless steel sheet can be stably improved. Meanwhile, the dislocation density of the retained austenite phase is 0.40 × 10 16 m -2 If it is less than that, dislocation movement within the phase cannot be sufficiently suppressed, which may lead to a decrease in strength and fatigue strength. Additionally, the upper limit of the dislocation density of the retained austenite phase is not particularly limited, but is preferably 5.0 × 10⁻⁶. 16 m -2 , more preferably 3.0×10 16 m -2 , more preferably 2.0×10 16 m-2 am.
[0090] Here, "dislocation density" refers to the electric field of dislocations contained within a unit volume of crystal. Typically, when cold rolling is performed, some of the moved dislocations accumulate within the material, thereby increasing the dislocation density. Since these accumulated dislocations interact with subsequent dislocations and inhibit their movement, an increase in dislocation density leads to improved strength and fatigue properties.
[0091] In addition, the dislocation density of the retained austenite phase can be calculated by analyzing the shape of the diffraction peaks measured by X-ray dilution through line profiling.
[0092] An austenitic stainless steel sheet according to an embodiment of the present invention may include inclusions having an average diameter of 1.5 μm or less. Coarse inclusions cause a decrease in the strength and fatigue strength of the austenitic stainless steel sheet, but if the inclusions are fine with an average diameter of 1.5 μm or less, the effect on the strength and fatigue strength of the austenitic stainless steel sheet can be suppressed.
[0093] Here, "inclusions" refers to non-metallic compounds such as oxides or sulfides.
[0094] The inclusions included in the austenitic stainless steel sheet according to an embodiment of the present invention are 1,000 pieces / mm 2 It is preferable that the number be less than or equal to this. By controlling the number of inclusions within this range, it becomes easier to stably improve the strength and fatigue strength of the austenitic stainless steel sheet. From the perspective of stably obtaining this effect, the number of inclusions is more preferably 980 pieces / mm². 2 Below, more preferably 960 pieces / mm 2 It is as follows. In addition, since it is desirable to have a small number of inclusions, the lower limit of the number of inclusions is not specifically limited.
[0095] Here, the number of inclusions can be determined by the point counting method in accordance with JIS G0555:2020.
[0096] The austenitic stainless steel sheet according to an embodiment of the present invention has a tensile strength (TS) of preferably 2200 MPa or more, more preferably 2250 MPa or more. By controlling the tensile strength within this range, the strength of the austenitic stainless steel sheet can be secured. In addition, the upper limit of the tensile strength is not particularly limited, but is generally 3000 MPa, preferably 2500 MPa.
[0097] Here, the tensile strength of the austenitic stainless steel sheet can be measured in accordance with JIS Z2241:2011.
[0098] The austenitic stainless steel sheet according to an embodiment of the present invention has an elongation at break (EL) of preferably 0.5% or more, more preferably 1.0% or more, and even more preferably 1.5%. By controlling the elongation at break within this range, the ductility of the austenitic stainless steel sheet can be secured. In addition, the upper limit of the elongation at break is not particularly limited, but is generally 10.0%, preferably 5.0%.
[0099] Here, the elongation at break of the austenitic stainless steel sheet can be measured in accordance with JIS Z2241:2011.
[0100] The austenitic stainless steel sheet according to an embodiment of the present invention has a fracture resistance number measured in accordance with JIS P8115:2001, preferably 1,100 times or more, more preferably 1,120 times or more, and even more preferably 1,130 times or more. With a fracture resistance number within this range, the fatigue strength of the austenitic stainless steel sheet can be said to be excellent. Furthermore, since fatigue strength is superior as the fracture resistance number increases, the upper limit value is not particularly limited.
[0101] Here, the number of internal sections can be measured in accordance with JIS P8115:2001 as described above.
[0102] The austenitic stainless steel sheet according to an embodiment of the present invention has a thickness of 0.15 mm or less, preferably 0.12 mm or less, more preferably 0.10 mm or less, and even more preferably 0.08 mm or less. By having such a thickness, thin-walled lightweighting of various parts can be achieved. In addition, the lower limit of the thickness can be adjusted according to the application and is not particularly limited, but is generally 0.01 mm.
[0103] The method for manufacturing an austenitic stainless steel sheet according to an embodiment of the present invention is not particularly limited as long as it is a method capable of providing an austenitic stainless steel sheet having the above characteristics. For example, a typical method for manufacturing an austenitic stainless steel sheet according to an embodiment of the present invention includes an intermediate rolling annealing process, a temper rolling process, and an aging treatment process.
[0104] The intermediate rolling annealing process is a process in which the steps of sequentially performing cold rolling and annealing are repeated two or more times for a hot-rolled annealed plate having the above composition. By performing the intermediate rolling annealing process, the grain size can be refined by generating a processing-induced martensite phase and then undergoing a reverse transformation, thereby improving strength.
[0105] Hot-rolled annealed sheets can be manufactured by melting stainless steel having the above composition, forging or casting it, hot-rolling it, and then annealing it. The conditions for hot rolling and annealing can be appropriately adjusted according to the composition of the stainless steel and are not particularly limited. In addition, after annealing, pickling or the like may be appropriately performed as needed.
[0106] The step of performing cold rolling and annealing sequentially is repeated two or more times. For example, if this step is performed three times, it is performed in the order of cold rolling-annealing-cold rolling-annealing-cold rolling-annealing. Therefore, even if the number of times this step is increased, the first step is cold rolling and the last step is annealing. The upper limit of the number of times this step is not specifically limited, but is generally 10 times, preferably 5 times.
[0107] The conditions for cold rolling at each stage can be appropriately adjusted according to the composition of the stainless steel and are not particularly limited, but it is preferable that the rolling reduction rate for each of the two or more cold rolling steps be 50% or more, more preferable that it be 55% or more, and even more preferable that it be 60% or more. By controlling the rolling reduction rate within such a range, it becomes easier to refine the grain size. In addition, the upper limit of each rolling reduction rate is not particularly limited, but for example, 80% or 90%.
[0108] The annealing conditions at each stage can be adjusted appropriately according to the composition of the stainless steel and are not particularly limited, but it is preferable that each annealing temperature be 900°C or higher, more preferable that it be 950°C or higher, and even more preferable that it be 1000°C or higher. By controlling the temperature within this range, it becomes easier to refine the grain size. In addition, the annealing temperatures at each stage may be the same or different. Furthermore, the upper limit of each annealing temperature is not particularly limited, but for example, it is 1200°C or 1300°C.
[0109] Also, each annealing time can be adjusted appropriately according to each annealing temperature, for example, 10 to 300 seconds.
[0110] The temper rolling process is a process of performing temper rolling on a cold-rolled annealed sheet obtained from an intermediate rolling annealing process at a rolling reduction rate of 60% or more to adjust the thickness to 0.15 mm or less. By performing the temper rolling process, deformation is accumulated in the austenite phase, and a certain amount of work-induced martensite phase can be secured, thereby improving strength.
[0111] The rolling reduction rate of temper rolling is preferably 62% or more, more preferably 65% or more, from the perspective of stably obtaining the above effect. The upper limit of this rolling reduction rate is not particularly limited, but is, for example, 80% or 90%.
[0112] The aging treatment process is a process of performing aging treatment under predetermined conditions on a tempered rolled plate obtained from a tempered rolling process. The aging treatment is as follows: (2):
[0113] B=T(log t+20) ··· (2)
[0114] It is performed under conditions where the value of B, expressed as (where T is temperature (K) and t is time (h)), is 11,500 to 15,000. By performing aging treatment under such conditions, strength can be improved through precipitation hardening by the austenite phase (γ phase).
[0115] The B value is preferably 12000 to 14800, more preferably 12500 to 14500, and even more preferably 13000 to 14000, from the perspective of stably obtaining the above effect. In addition, the temperature and time of the aging treatment are not particularly limited as long as the above conditions are satisfied, but the typical temperature is 300 to 700℃ and the typical time is 5 to 500 seconds.
[0116] The austenitic stainless steel sheet according to an embodiment of the present invention has high strength and excellent fatigue characteristics. Therefore, it can be used in various parts where thin-walled, lightweight construction is required, such as structural or functional parts in communication devices like smartphones or precision devices like computers. In particular, the austenitic stainless steel sheet according to an embodiment of the present invention is suitable for use in a plate spring used in a back plate that supports the folding function of a liquid crystal screen in a foldable smartphone (foldable phone), etc.
[0117] [Example]
[0118] The contents of the present invention will be described in detail below with reference to examples, but the present invention is not to be interpreted as being limited to these examples.
[0119] 30 kg of stainless steel having the composition shown in Table 1 was melted in a vacuum melting furnace, forged into a plate shape with a thickness of 30 mm, heated at 1230°C for 2 hours, and hot-rolled to obtain a hot-rolled plate with the thickness shown in Table 2. Next, the hot-rolled plate was annealed and pickled to become a hot-rolled annealed plate, and then an intermediate rolling annealing process, a temper rolling process, and an aging treatment process were sequentially performed on the hot-rolled annealed plate to obtain an austenitic stainless steel plate. The conditions for the intermediate rolling annealing process, the temper rolling process, and the aging treatment process are shown in Table 2. In addition, each annealing condition in the intermediate rolling annealing process was set to 1050°C × 60 seconds.
[0120]
[0121]
[0122] The following evaluation was performed on the austenitic stainless steel sheet obtained as described above.
[0123] Average crystal size
[0124] The average crystal grain size was determined by a comparative method in accordance with JIS G0551:2020. The observation surface of the average crystal grain size was obtained by electrolytically polishing the surface of an austenitic stainless steel sheet to a mirror finish, and then etching it with aqua regia.
[0125] Content of processed organic martensite phase
[0126] A test specimen was cut from an austenitic stainless steel sheet, and the content of processing-induced martensite was measured using a ferritescope (FERITESCOPE MP30E-S manufactured by Fischer). Measurements were taken at any three locations on the surface of the test specimen, and the average value was used as the result. Additionally, the processing-induced martensite phase may be abbreviated as "M phase" below.
[0127] Dislocation density of the retained austenite phase
[0128] The dislocation density of the retained austenite phase was calculated by analyzing the shape of diffraction peaks measured by X-ray dilution using line profiling. In a microstructure where dislocations are introduced, lattice deformation occurs around the dislocations, and small-angle grain boundaries and cell structures develop based on the arrangement of the dislocations. By identifying these structures using X-rays, the dislocation density can be calculated.
[0129] Test specimens were used that were cut from an austenitic stainless steel plate at an arbitrary location and subjected to mechanical polishing and chemical polishing.
[0130] X-ray dilution was performed on the surface structure of this test specimen, and the dislocation density ρ was calculated from the single diffraction peak of {111} of the retained austenite phase. The following equation (3) was used to calculate the dislocation density ρ.
[0131] ρ=[3(2π) 1 / 2 <ε 2 > 1 / 2 ] / Db ··· (3)
[0132] Among the foods, <ε 2> represents the mean squared variant, D is the determinant size, and b is the Burgers vector.
[0133] Also, the squared mean strain <ε used in Equation (3) 2 The size of the determinant D and the determinant size D were obtained from the following equation (4).
[0134] -lnA(L) / L=1 / D+[-1 / (2D 2 )+2π 2 <ε 2 >h0 2 / a 2 ]L ··· (4)
[0135] In the equation, lnA(L) is the logarithm of the Fourier coefficients of the line profile of each diffraction peak, L is the Fourier length, h0 2 =h 2 +k 2 +l 2 (h, k, l are the plane indices of the diffraction peaks used), and a is the lattice constant. Let the vertical axis be -lnA(L) / L and the horizontal axis be L, and D be derived from the y-intercept 1 / D of the plot, and the gradient [-1 / (2D 2 )+2π 2 <ε 2 >h0 2 / a 2 From ] <ε 2 Saved >
[0136] In addition, an X-ray diffraction device (manufactured by Rigaku Co., Ltd.) was used as the analysis device, and a Cu dry ball was used as the target. Also, in the following, the retained austenite phase may be abbreviated as "γ phase".
[0137] <Average diameter and number of inclusions>
[0138] The average diameter and number of inclusions were determined by the point calculation method in accordance with JIS G0555:2020. The surface of the inclusions was obtained by mirror-finishing the surface of an austenitic stainless steel sheet through electrolytic polishing.
[0139] <Tensile Strength (TS) and Elongation at Break (EL)>
[0140] A JIS No. 13B test specimen was cut from an austenitic stainless steel plate, and measurements were performed using this test specimen in accordance with JIS Z2241:2011.
[0141] <Number of intercourses>
[0142] The number of internal cuts was measured in accordance with JIS P8115:2001. For the measurement of the number of internal cuts, a test specimen measuring 15 mm (width direction) × 130 mm (rolling direction) was used under the following conditions.
[0143] Load: 0.25kgf
[0144] Test speed: 175 cpm
[0145] Bending angle: 135°
[0146] R of bending clamp: 2.0mm
[0147] Bending clamp opening: 0.25mm
[0148] The results of each evaluation above are shown in Table 3.
[0149]
[0150] As shown in Table 3, the austenitic stainless steel sheets of Examples 1 to 11 were found to have high strength and excellent fatigue properties, as evidenced by their high tensile strength (TS), elongation at break (EL), and number of breaks.
[0151] In this regard, the austenitic stainless steel sheet of Comparative Example 1 had too low Si and Mo content and too high Cr content, so Md 30 The value of became too large. As a result, TS, EL, and the number of internal cuts decreased.
[0152] Because the austenitic stainless steel sheet of Comparative Example 2 had too high Si and Cu content, Md 30 The value of became too small. As a result, TS and the number of internal cuts decreased.
[0153] The austenitic stainless steel sheets of Comparative Examples 3 and 4 had their thickness and average grain size increased because the number of intermediate rolling and annealing steps was reduced. As a result, the TS and the number of cuts decreased.
[0154] The austenitic stainless steel sheet of Comparative Example 5 had a lower TS value because the value of B was too small during the aging treatment process.
[0155] In the austenitic stainless steel sheet of Comparative Example 6, the dislocation density of the γ phase decreased because the value of B was too high during the aging treatment process. As a result, the TS decreased.
[0156] In the austenitic stainless steel sheet of Comparative Example 7, the rolling reduction rate in the temper rolling process was too low, so the content of the M phase and the dislocation density of the γ phase decreased. As a result, the TS decreased.
[0157] The austenitic stainless steel sheet of Comparative Example 8 had too high an O content, which resulted in a large number of inclusions. Consequently, the number of cuts decreased.
[0158] As can be seen from the above results, the present invention provides an austenitic stainless steel sheet having high strength and excellent fatigue properties even with a small thickness, and a method for manufacturing the same.
[0159] In addition, according to the present invention, a leaf spring with high strength and a long lifespan can be provided even with a small thickness.
[0160] In addition, based on the above results, the present invention may be made in the following forms.
[0161] [1] Based on mass, it contains C: 0.04~0.11%, Si: 2.0~3.5%, Mn: 1.50% or less, Ni: 6.0~10.0%, Cr: 12.0~15.0%, Mo: 1.3~3.2%, Cu: 1.00% or less, N: 0.03~0.15%, O: 0.0050% or less, and the remainder is Fe and impurities, and the following formula (1):
[0162] Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo ··· (1)
[0163] Md represented by (in the formula, the element symbol indicates the content (mass%) of each element) 30 It has a composition with a value of -30 to 0℃, and
[0164] It has a metal structure having a processed organic martensite phase content of 30.0 volume% or more, and also
[0165] Austenitic stainless steel sheet with a thickness of 0.15 mm or less.
[0166] [2] The austenitic stainless steel described in [1] further comprising, on a mass basis, one or more selected from Co: 0.05~0.50%, Al: 0.15% or less, V: 0.0001~0.5000%, Ti: 0.01~0.50%, B: 0.0001~0.0150%, Nb: 0.001~0.100%, Mg: 0.0001~0.0030%, Ca: 0.0003~0.0100%, Sn: 0.001~0.500%, Pb: 0.0001~0.0100%, W: 0.0001~0.5000%, Zr: 0.0001~0.1000%, REM: 0.0001~0.3000%. Steel plate.
[0167] [3] An austenitic stainless steel sheet as described in [1] or [2], having an average crystal grain size of 15.0 μm or less.
[0168] [4] The dislocation density of the residual austenite phase is 0.40×10 16 m-2 The austenitic stainless steel sheet described in any one of [1] to [3] above.
[0169] [5] An austenitic stainless steel sheet described in any one of [1] to [4] containing inclusions with an average diameter of 1.5 μm or less.
[0170] [6] The above inclusions are 1000 pieces / mm 2 The austenitic stainless steel sheet described in [5] below.
[0171] [7] An austenitic stainless steel sheet having a tensile strength (TS) of 2200 MPa or more, as described in any one of [1] to [6].
[0172] [8] An austenitic stainless steel sheet as described in any one of [1] to [7], having an elongation at break (EL) of 0.5% or more.
[0173] [9] An austenitic stainless steel sheet as described in any one of [1] to [8], having a cutting count of 1,100 or more as measured in accordance with JIS P8115:2001.
[0174]
[10] By mass, it contains C: 0.04~0.11%, Si: 2.0~3.5%, Mn: 1.50% or less, Ni: 6.0~10.0%, Cr: 12.0~15.0%, Mo: 1.3~3.2%, Cu: 1.00% or less, N: 0.03~0.15%, O: 0.0050% or less, and the remainder is Fe and impurities, and the following formula (1):
[0175] Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo ··· (1)
[0176] Md represented by (in the formula, the element symbol indicates the content (mass%) of each element) 30For a hot-rolled annealed plate having a composition in which the value of is -30 to 0℃, an intermediate rolling annealing process in which the step of sequentially performing cold rolling and annealing is repeated two or more times, and
[0177] A temper rolling process for a cold-rolled annealed plate obtained from the above intermediate rolling annealing process, wherein temper rolling is performed at a rolling reduction rate of 60% or more to adjust the thickness to 0.15mm or less, and
[0178] For the tempered rolled plate obtained from the above tempered rolling process, the following formula (2):
[0179] B=T(log t+20) ··· (2)
[0180] An aging treatment process in which the value of B, expressed by (where T is temperature (K) and t is time (h)), is 11,500 to 15,000.
[0181] A method for manufacturing an austenitic stainless steel sheet, comprising
[0182]
[11] The hot-rolled annealed plate further comprises, by mass, one or more selected from Co: 0.05~0.50%, Al: 0.15% or less, V: 0.0001~0.5000%, Ti: 0.01~0.50%, B: 0.0001~0.0150%, Nb: 0.001~0.100%, Mg: 0.0001~0.0030%, Ca: 0.0003~0.0100%, Sn: 0.001~0.500%, Pb: 0.0001~0.0100%, W: 0.0001~0.5000%, Zr: 0.0001~0.1000%, REM: 0.0001~0.3000%,
[10] A method for manufacturing an austenitic stainless steel sheet.
[0183]
[12] A method for manufacturing an austenitic stainless steel sheet as described in
[10] or
[11] , wherein each of the two or more cold rolling steps in the above intermediate rolling annealing process has a rolling reduction rate of 50% or more.
[0184]
[13] A method for manufacturing an austenitic stainless steel sheet as described in any one of
[10] to
[12] , wherein the aging time in the above aging treatment process is 5 to 500 seconds.
[0185]
[14] A plate spring comprising an austenitic stainless steel plate as described in any one of [1] to [9].
Claims
Claim 1 Based on mass, it contains C: 0.04~0.11%, Si: 2.0~3.5%, Mn: 0.01~1.50%, Ni: 6.0~10.0%, Cr: 12.0~15.0%, Mo: 1.3~3.2%, Cu: 0.01~1.00%, N: 0.03~0.15%, O: 0.0001~0.0050%, and the remainder consists of Fe and impurities, and the following formula (1): Md 30 Md represented by =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo ··· (1) (wherein the formula, the element symbols indicate the content (mass%) of each element) 30 It has a composition with a value of -30 to 0°C, a metallic structure with a content of 30.0 volume% or more of the processing-induced martensite phase, an average crystal grain size of 15.0 μm or less, and a dislocation density of the retained austenite phase of 0.40 × 10⁻⁶ 16 m -2 Above, 1,000 inclusions / mm² with an average diameter of 1.5 μm or less 2 Austenitic stainless steel sheet having a thickness of 0.15 mm or less. Claim 2 The austenitic stainless steel of claim 1, further comprising, by mass, one or more selected from Co: 0.05~0.50%, Al: 0.15% or less, V: 0.0001~0.5000%, Ti: 0.01~0.50%, B: 0.0001~0.0150%, Nb: 0.001~0.100%, Mg: 0.0001~0.0030%, Ca: 0.0003~0.0100%, Sn: 0.001~0.500%, Pb: 0.0001~0.0100%, W: 0.0001~0.5000%, Zr: 0.0001~0.1000%, and REM: 0.0001~0.3000%. Steel plate. Claim 3 An austenitic stainless steel sheet according to claim 1 or claim 2, having a tensile strength (TS) of 2200 MPa or more. Claim 4 An austenitic stainless steel sheet according to claim 1 or claim 2, wherein the elongation at break (EL) is 0.5% or more. Claim 5 An austenitic stainless steel sheet according to claim 1 or claim 2, having a fracture resistance of 1,100 or more as measured in accordance with JIS P8115:2001. Claim 6 Based on mass, it contains C: 0.04~0.11%, Si: 2.0~3.5%, Mn: 0.01~1.50%, Ni: 6.0~10.0%, Cr: 12.0~15.0%, Mo: 1.3~3.2%, Cu: 0.01~1.00%, N: 0.03~0.15%, O: 0.0001~0.0050%, and the remainder consists of Fe and impurities, and the following formula (1): Md 30 Md represented by =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo ··· (1) (wherein the formula, the element symbols indicate the content (mass%) of each element) 30 For a hot-rolled annealed plate having a composition with a value of -30 to 0°C, an intermediate rolling annealing process is performed by repeating the step of sequentially performing cold rolling with each rolling reduction rate of 50% or more and 90% or less, and annealing with each annealing temperature of 900°C or more and 1300°C or less and each annealing time of 10 to 300 seconds at least twice; for the cold-rolled annealed plate obtained from the intermediate rolling annealing process, a temper rolling process is performed with a rolling reduction rate of 60% or more to adjust the thickness to 0.15 mm or less; and for the temper rolled plate obtained from the temper rolling process, for 5 to 500 seconds under the condition that the value of B, represented by the following equation (2): B=T(log t+20) ··· (2) (wherein T is temperature (K) and t is time (h)), becomes 11500 to 15000. A method for manufacturing an austenitic stainless steel sheet, comprising an aging treatment process for performing aging treatment. Claim 7 In claim 6, the hot-rolled annealed plate further comprises, by mass, one or more selected from Co: 0.05~0.50%, Al: 0.15% or less, V: 0.0001~0.5000%, Ti: 0.01~0.50%, B: 0.0001~0.0150%, Nb: 0.001~0.100%, Mg: 0.0001~0.0030%, Ca: 0.0003~0.0100%, Sn: 0.001~0.500%, Pb: 0.0001~0.0100%, W: 0.0001~0.5000%, Zr: 0.0001~0.1000%, and REM: 0.0001~0.3000%. Method for manufacturing austenitic stainless steel sheets. Claim 8 A plate spring comprising an austenitic stainless steel plate as described in claim 1 or claim 2. Claim 9 delete Claim 10 delete Claim 11 delete Claim 12 delete Claim 13 delete Claim 14 delete
Citation Information
Patent Citations
Austenitic stainless steel material, method for producing same, and plate spring
WO2021230244A1